Tunable properties of self-Assembled polyurethane using two-Dimensional nanoparticles: Potential nano-biohybrid - Mishra A.; Purkayastha B.P.D.; Roy J.K.; Aswal V.K.; Maiti P. (My University, 2025)
Nanostructure, key to property alteration, has been widely diverse by using two-dimensional nanoparticle in different stages of polymerization. Molecular level self-assembly starting from nanoscale 2-D molecular sheet to optically observable microscale crystallite has been unraveled stepwise for thermoplastic elastomer for the first time. The nature of self-assembly can be tuned by judicious choice of polymerization procedure in the presence of organically modified nanoclay. The effect of modulated nanostructure and self-assembly has been explored for the unusual property enhancement including electronic, thermal, mechanical, barrier, and biological (genotoxicity). Both the stiffness and toughness increase in nano-biohybrid without any trade-off. The unique splintering phenomenon and its variation under a dynamic frequency have been investigated by changing the synthesizing route of nanohybrids using a fixed concentration of nanoparticle. For understanding the controlled cellular responses to the implant new hybrid materials, cell adhesion and detailed genotoxicity reveal total biological recognition of the developed nano-biohybrids. © 2010 American Chemical Society.